2005
DOI: 10.1063/1.2001752
|View full text |Cite
|
Sign up to set email alerts
|

Segregation of nearest-neighbor donor-pair defects to Si∕SiO2 interfaces

Abstract: We perform first-principles density-functional calculations to study the stability of donor-pair defects at Si∕SiO2 interfaces. For P dopants, individual dopant atoms energetically favor Si lattice sites in the interface region, as compared to bulk Si. When dopant atoms aggregate to the interface region at very high dopant concentrations, dopant segregation occurs in form of electrically deactivating nearest-neighbor donor pairs that comprise two threefold coordinated dopant atoms. Our defect model explains bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 20 publications
(15 reference statements)
3
10
0
Order By: Relevance
“…30 Pair formation is driven by the tendency of neutral dopant atoms to establish their preferred threefold coordination as in PH 3 and AsH 3 molecules. Pairing was also later suggested 27,28,31 to occur at the Si-SiO 2 interface in order to explain the observed dopant pile up for higher implanted doses. 27 We found that a nearest-neighbor P-P pair just below the interface plane lowers its energy ͑by 0.23 eV with respect to two isolated P dopants͒ by breaking the P-P bond ͑P-P distance of 3.28 Å͒ and achieving a threefold coordination for the two dopant atoms ͓Fig.…”
Section: Dopant Segregationmentioning
confidence: 93%
See 1 more Smart Citation
“…30 Pair formation is driven by the tendency of neutral dopant atoms to establish their preferred threefold coordination as in PH 3 and AsH 3 molecules. Pairing was also later suggested 27,28,31 to occur at the Si-SiO 2 interface in order to explain the observed dopant pile up for higher implanted doses. 27 We found that a nearest-neighbor P-P pair just below the interface plane lowers its energy ͑by 0.23 eV with respect to two isolated P dopants͒ by breaking the P-P bond ͑P-P distance of 3.28 Å͒ and achieving a threefold coordination for the two dopant atoms ͓Fig.…”
Section: Dopant Segregationmentioning
confidence: 93%
“…The energy gain arises from relaxations of the near-interface oxide network ͓as depicted in Fig. 6͑b͒, two O-bridge atoms are displaced toward the Si substrate by 0.2 Å͔, a fact that previous computational studies 27,28,31 of dopant segregation to the Si-SiO 2 interface overlooked. The binding energy for this pair is 0.15 eV ͑with respect to two isolated P atoms in bulk Si͒.…”
Section: Dopant Segregationmentioning
confidence: 98%
“…In contrast to previous firstprinciples calculations [20][21][22][23][24][25] that focus on defect configurations within a monolayer of the interface that passivate the donor and favour segregation, our emphasis is on understanding electrically active arsenic impurities in bulk-like, four-fold coordinated configurations at and near the interface.…”
Section: Introductionmentioning
confidence: 99%
“…15 As the temperature increases, the phosphorus trapped at the grain boundaries 78 diffuses back into the silicon grains and increases the carrier concentration.…”
Section: Synthesis Of Nanocrystalline Silicon Thermoelectrics Withmentioning
confidence: 99%